2016
DOI: 10.1016/j.plaphy.2016.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting ethylene perception with 1-methylcyclopropene triggers molecular responses aimed to cope with cell toxicity and increased respiration in citrus fruits

Abstract: The ethylene perception inhibitor 1-methylcyclopropene (1-MCP) has been critical in understanding the hormone's mode of action. However, 1-MCP may trigger other processes that could vary the interpretation of results related until now to ethylene, which we aim to understand by using transcriptomic analysis. Transcriptomic changes in ethylene and 1-MCP-treated 'Navelate' (Citrus sinensis L. Osbeck) oranges were studied in parallel with changes in ethylene production, respiration and peel damage. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 36 publications
9
28
0
Order By: Relevance
“…Simultaneous synthesis and degradation of sucrose during postharvest storage of fruits has been well described (Duque et al, 1999;Zhu et al, 2013). A link between ethylene and sucrose metabolism is suggested by increased gene transcript and enzymatic activity of SPS by exogenous ethylene treatment or during postharvest ripening (Duque et al, 1999;Choudhury et al, 2008;Lombardo et al, 2011). Sucrose treatment of tomato fruits advanced ripening, and increased expression of genes involved in both sugar biosynthesis and degradation .…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous synthesis and degradation of sucrose during postharvest storage of fruits has been well described (Duque et al, 1999;Zhu et al, 2013). A link between ethylene and sucrose metabolism is suggested by increased gene transcript and enzymatic activity of SPS by exogenous ethylene treatment or during postharvest ripening (Duque et al, 1999;Choudhury et al, 2008;Lombardo et al, 2011). Sucrose treatment of tomato fruits advanced ripening, and increased expression of genes involved in both sugar biosynthesis and degradation .…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…Decreased sucrose accumulation was associated with a down-regulation of two sucrose transporters (SUC11 and SUC12), whose expression is triggered at veraison when grape berries start to accumulate sugars. In citrus, 1-MCP repressed genes involved in starch synthesis and degradation and increased the expression levels of SuSy genes (Estables-Ortiz et al, 2016). In grapes, and another non-climacteric fruit, strawberry, it has been proposed that sucrose functions as a signal that acts upstream of the ABA signaling pathway, thus playing an important role in the regulation of fruit ripening (Jia et al, 2013;Jia et al, 2017).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…1-MCP led to membrane and cellular damage, and also to a peel damage disorder called nonchilling peel pitting (NCPP). This disorder is manifested as depressed damaged areas on peel 5,6 ( Supplementary Fig. S1).…”
mentioning
confidence: 99%
“…In the present work, we found very marked changes in the genes that encode FAD-dependent oxidoreductases, in abundant GSTs, ABC transporters, and also in different transcription factors, which were only induced in non-conditioned fruits in response to cold stress (Table S1). These genes are regulated in citrus fruits by ethylene (Establés-Ortiz et al, 2016). However, the comparison of the changes in the transcriptome of the flavedo of chilling-exposed fruits with those previously identified in our laboratory when studying the effect of exogenous ethylene (Establés-Ortiz et al, 2016) have shown that the percentage of genes regulated by both chilling and ethylene did not exceed 15% (Establés-Ortiz, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…These genes are regulated in citrus fruits by ethylene (Establés-Ortiz et al, 2016). However, the comparison of the changes in the transcriptome of the flavedo of chilling-exposed fruits with those previously identified in our laboratory when studying the effect of exogenous ethylene (Establés-Ortiz et al, 2016) have shown that the percentage of genes regulated by both chilling and ethylene did not exceed 15% (Establés-Ortiz, 2008). Therefore, this is in line with our previous idea that most protective mechanisms of citrus fruits against chilling do not depend on ethylene.…”
Section: Resultsmentioning
confidence: 99%